Method for preparing ZnMgO ferroelectric film nonvolatile memory by ALD (atomic layer deposition) process
The preparation of ZnMgO ferroelectric thin films by ALD process solves the problems of uneven film quality and numerous defects in existing technologies, realizing high-performance non-volatile memory suitable for high aspect ratio structures and industrial production.
Patent Information
- Application Number
- CN202510881830.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-11-07
AI Technical Summary
Existing methods for preparing ZnMgO ferroelectric thin films are difficult to precisely control the film quality, resulting in numerous internal defects, high resistivity, and uneven dielectric constant, which affect the performance and reliability of memory.
Atomic layer deposition (ALD) was employed to form a buffer layer by magnetron sputtering, combined with diethylzinc and bis(2,2,6,6,-tetramethyl-3,5-heptadecanoic acid) magnesium as precursors to control the deposition of Zn and Mg. Quadrupole mass spectrometry was used to monitor and adjust the precursor pulse time to achieve atomic-level precise control.
High-quality, uniformly composed ZnMgO ferroelectric thin films were prepared, which improved the electrical performance and reliability of memory, were adaptable to high aspect ratio structure deposition, reduced production costs, and were suitable for industrial production.
Smart Images

Figure CN120916439A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of memory technology, and in particular to a method for preparing a non-volatile ZnMgO ferroelectric thin film memory using the ALD process. Background Technology
[0002] Currently, the memory field is rapidly evolving towards high performance, high integration, low power consumption, and non-volatility. Against this backdrop, ferroelectric RAM (FeRAM) exhibits significant advantages. Compared to traditional memory technologies, FeRAM, based on the spontaneous polarization characteristics of ferroelectric materials, possesses high-speed read and write capabilities, with write speeds reaching nanosecond levels, far exceeding Flash memory. It also exhibits non-volatility, allowing data to be retained long-term after power loss, and high durability, solving the problems of volatility in traditional Dynamic Random Access Memory (DRAM) and insufficient durability in Flash memory. Furthermore, FeRAM excels in low power consumption, requiring only one-tenth the energy of DRAM, meeting the urgent needs of IoT and wearable devices for low-power storage. In terms of integration processes, FeRAM's excellent compatibility with CMOS technology enables high-density integration, providing a feasible path for the miniaturization and high performance of future memory technologies, and showing broad application prospects in emerging fields such as artificial intelligence edge computing and embedded systems.
[0003] Ferroelectric thin films are the core component of ferroelectric memories. With their spontaneous polarization characteristics, they correspond to the binary "0" and "1" in two polarization directions, respectively, thus becoming the carrier of data storage. Furthermore, due to the non-volatility of polarization reversal, they can retain data after power failure. At the same time, ferroelectric thin films have a fast polarization reversal speed (nanosecond level), enabling high-speed read and write operations comparable to DRAM. Their performance directly determines the data storage and read / write capabilities of ferroelectric memories.
[0004] Against the backdrop of the rapid development of non-volatile memory technology, Zn-Mg-O (ZnMgO) based ferroelectric thin films have attracted widespread attention due to their unique polarization properties. Research indicates that by precisely controlling the Mg... 2+ The doping concentration can induce a metastable structure with reversible spontaneous polarization in the ZnO lattice, giving it significant ferroelectricity at room temperature. Compared to traditional lead-containing ferroelectric materials (such as PZT), this system not only possesses a higher dielectric constant, a larger remanent polarization field, a lower leakage current density, and a higher Curie temperature, but also exhibits CMOS process compatibility and environmental friendliness, demonstrating unique advantages in fields such as 3D NAND architecture memories and neuromorphic synaptic devices.
[0005] However, in the prior art, the common preparation method of ZnMgO ferroelectric thin film, such as radio frequency magnetron sputtering method, in the preparation process, the atoms or molecules are sputtered from the target material and deposited on the substrate to form a thin film by high-energy particle bombardment of the target material. This method is difficult to accurately control the deposition process of atoms, resulting in poor quality of the thin film. Specifically, a large number of defects, such as grain boundary defects, oxygen vacancies, etc., are easily generated in the thin film. The existence of these defects destroys the integrity of the crystal structure of the thin film, and further affects its electrical properties. When applied to ferroelectric memory, it will cause the resistivity of the thin film to rise, which will greatly hinder the charge transmission process and reduce the read-write speed of the memory. At the same time, the grain boundary defects may also cause uneven local electric field distribution, affecting the stability of the polarization state of the ferroelectric thin film, and causing the reliability of the stored data to decrease.
[0006] Another commonly used preparation method is chemical solution deposition method, although the equipment is simple and the cost is low, but in the process, the concentration, temperature, reaction time and other factors of the solution have great influence on the quality of the thin film, and it is difficult to accurately control. This makes the composition uniformity of the prepared ZnMgO ferroelectric thin film poor, and the Mg element doping ratio in different regions deviates. In the ferroelectric memory, this composition inhomogeneity will cause the dielectric constant of the thin film to differ at different positions, affecting the consistency between the storage units, and is not conducive to realizing high-density storage. In addition, the thin film prepared by the chemical solution deposition method usually needs high-temperature annealing treatment to improve the crystalline quality, however, the high-temperature process is easy to introduce impurities, which further deteriorates the electrical properties of the thin film.
[0007] The existing ZnMgO ferroelectric thin film preparation technology has defects in the quality of the thin film, electrical properties, process complexity, etc. Therefore, it is necessary to propose a method for preparing ZnMgO ferroelectric thin film non-volatile memory by ALD process to solve the above problems. SUMMARY
[0008] The purpose of the present application is to provide a method for preparing ZnMgO ferroelectric thin film non-volatile memory by ALD process, to solve the problems of many defects, high resistivity, and non-uniform dielectric constant in the prior art.
[0009] The present application provides a method for preparing ZnMgO ferroelectric thin film non-volatile memory by ALD process, comprising: S1: depositing a buffer layer on a p-type silicon substrate by a magnetron sputtering process; S2: depositing a ZnMgO ferroelectric thin film layer on the buffer layer by an atomic layer deposition process; S3: depositing a top electrode layer on the ZnMgO ferroelectric thin film layer, and performing a patterning process on the top electrode layer by a photolithography and stripping process, and exposing part of the ZnMgO ferroelectric thin film layer; S4: performing patterning treatment on the exposed part of the ZnMgO ferroelectric thin film layer by means of photolithography and stripping process, and finally forming a ferroelectric memory.
[0010] In a possible embodiment, in the atomic layer deposition process of step S2, diethyl zinc is used as the precursor of zinc, and bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium or diethyl magnesium is used as the precursor of magnesium, wherein the diethyl zinc is not subjected to heating treatment, and the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is heated to 135-145℃.
[0011] In a possible embodiment, when bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the precursor of magnesium, deionized water is used as the oxidizing source. When diethyl magnesium is used as the precursor of magnesium, oxygen plasma is used as the oxidizing source.
[0012] In a possible embodiment, in the atomic layer deposition process of step S2, the carrier gas is argon. When bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the precursor of magnesium, the flow rate of the carrier gas ranges from 170 sccm to 230 sccm, and the system pressure ranges from 0.16 Torr to 0.18 Torr. When diethyl magnesium is used as the precursor of magnesium, the flow rate of the carrier gas ranges from 270 sccm to 330 sccm.
[0013] In a possible embodiment, in the atomic layer deposition process of step S2, a single cycle of ZnO includes the following processing steps in sequence: 0.05 s diethyl zinc pulse, 10 s argon purge, 0.05 s deionized water pulse, 10 s argon purge.
[0014] In a possible embodiment, when bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the precursor of magnesium, a single cycle of MgO includes the following processing steps in sequence: 0.8 s bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium pulse, 15 s argon purge, 0.05 s deionized water pulse, 15 s argon purge. When diethyl magnesium is used as the precursor of magnesium, a single cycle of MgO includes the following processing steps in sequence: 0.8 s diethyl magnesium pulse, 15 s argon purge, 0.05 s deionized water pulse, 15 s argon purge.
[0015] In a possible embodiment, in the atomic layer deposition process of step S2, a single supercycle comprises N times of ZnO cycles and 1 time of MgO cycle, by controlling the pulse time of the zinc precursor, the pulse time of the magnesium precursor and the cycle number N, the doping concentration of magnesium in the ZnMgO film can be adjusted, wherein N is a positive integer.
[0016] In a possible embodiment, after the supercycle deposition is completed, the ZnMgO ferroelectric film layer is rapidly heat annealed at 400℃ for 10 min in an oxygen atmosphere.
[0017] In a possible embodiment, the process cavity of the atomic layer deposition device is integrated with a quadrupole mass spectrometer and a control adjustment system; In the atomic layer deposition process of step S2, the quadrupole mass spectrometer monitors the signal intensity ratio of Zn and C2H6 and the signal intensity ratio of Mg and C4H 10 in the tail gas in real time, and the control adjustment system dynamically adjusts the pulse time of the zinc precursor and the pulse time of the magnesium precursor according to the monitoring result of the quadrupole mass spectrometer.
[0018] In a possible embodiment, the buffer layer is an Al2O3 layer, a ZnO layer or a gradient component Al x Zn 1-x O gradient layer, wherein x is greater than 0 and less than 1.
[0019] The method for preparing the ZnMgO ferroelectric film nonvolatile memory by the ALD process has the beneficial effects that: by the unique self-limiting surface reaction mechanism of the ALD process, atomic-level accurate control is realized, so that the ZnMgO ferroelectric film with high quality, uniform composition and excellent electrical performance is prepared, the problems such as many film defects, high resistivity, non-uniform dielectric constant and difficulty in adapting to high aspect ratio structure deposition in the prior art are effectively solved, the performance and reliability of the ferroelectric memory are improved, and the increasing storage demand is met. The simple and low-cost process method proposed in the application is suitable for industrial production. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 The text flowchart of the method for preparing the ZnMgO ferroelectric film nonvolatile memory by the ALD process of the application.
[0021] Figure 2 The process flowchart of the method for preparing the ZnMgO ferroelectric film nonvolatile memory by the ALD process of the application.
[0022] Figure 3 The schematic diagram of the ferroelectric memory prepared by the method for preparing the ZnMgO ferroelectric film nonvolatile memory by the ALD process of the application.
[0023] Explanation of reference signs: silicon substrate 510; buffer layer 520; ZnMgO ferroelectric thin film layer 530; top electrode layer 540. DETAILED DESCRIPTION
[0024] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are some but not all of the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0025] In view of the problems in the prior art, referring to Figure 1 and Figure 2 the embodiments of the present application provide a preparation method of a ZnMgO ferroelectric thin film-based nonvolatile memory, which comprises the following steps: S1: forming a buffer layer 520 on a p-type silicon substrate 510 by a magnetron sputtering process, and the buffer layer 520 serves as a gate dielectric.
[0026] Specifically, the silicon substrate 510 is a silicon wafer, the crystal orientation of the silicon substrate 510 is 100, the resistivity of the silicon substrate 510 ranges from 1 Ω·cm to 10 Ω·cm, and the thickness of the natural oxide layer on the surface of the silicon substrate 510 ranges from 1.4 nm to 1.5 nm.
[0027] S2: forming a ZnMgO ferroelectric thin film layer 530 on the buffer layer 520 by an atomic layer deposition process; S3: forming a top electrode layer 540 on the ZnMgO ferroelectric thin film layer 530 by an electron beam evaporation process, performing a patterning process on the top electrode layer 540 by a photolithography and stripping process, and exposing part of the ZnMgO ferroelectric thin film layer 530.
[0028] S4: performing a patterning process on the exposed part of the ZnMgO ferroelectric thin film layer 530 by a photolithography and stripping process, and finally forming a ferroelectric memory, as shown in Figure 3 .
[0029] Before step S1, the method further comprises step S0: performing a surface cleaning process on the silicon substrate 510 by using hydrofluoric acid (HF) to remove the natural oxide layer (SiO2) on the surface of the silicon substrate 510.
[0030] The buffer layer 520 is used as a gate dielectric, and the traditional bottom electrode is omitted. The preparation of the traditional bottom electrode usually requires additional process steps, such as sputtering, photolithography, and stripping. Omitting the traditional bottom electrode can reduce these steps, simplify the process flow, and reduce production costs and complexity. The top electrode is deposited directly on the ZnMgO ferroelectric thin film layer 530, and then the top electrode preparation and device structure integration are performed. The top electrode is deposited by electron beam evaporation, and the patterned top electrode is formed by photolithography and stripping, finally forming a metal-ferroelectric-insulator-semiconductor structure.
[0031] During the entire preparation process, compared with other deposition methods and patterning processes, this process not only has simple preparation steps, low cost and high compatibility with traditional transistor processes, but also has high overall device yield, and the actual yield on amorphous silicon wafer can reach more than 95%.
[0032] Atomic layer deposition (ALD) has the advantages of atomic-level thickness control, high composition uniformity, and excellent step coverage due to its self-limiting surface reaction mechanism, making it an ideal technology for preparing high-quality ferroelectric thin films. The self-limiting reaction characteristics of ALD ensure constant deposition amount per cycle, enabling atomic-level precision component control. The layer-by-layer growth characteristics of ALD can inhibit the element segregation and oxygen vacancy defects commonly found in traditional sputtering or solution methods. For example, the Mg segregation caused by the difference in element sputtering yield in magnetron sputtering can be improved by precise control of pulse sequence and flow in ALD. The three-dimensional conformal deposition capability of ALD is suitable for high aspect ratio structures (such as deep holes or sidewalls of three-dimensional memory), solving the problem of thickness non-uniformity in traditional processes (such as sputtering / solution method) in three-dimensional structures, which is crucial for the uniformity of ferroelectric memory cells.
[0033] In one embodiment, the buffer layer 520 is an Al2O3 layer, a ZnO layer, or a gradient layer of Al x Zn 1-x O, where x is greater than 0 and less than 1.
[0034] The lattice constant of Si (about 0.543 nm) is significantly different from that of ZnMgO (hexagonal system, a = 0.325 nm), resulting in a lattice mismatch of more than 20%. This mismatch can generate a large interfacial stress during thin film growth, causing dislocations and defects, which affect the quality and performance of the thin film. This scheme introduces Al2O3 or ZnO as a buffer layer 520 by magnetron sputtering, both Al2O3 (lattice constant of 0.4758 nm) and ZnO (hexagonal system, a = 0.325 nm) have a lattice constant closer to that of ZnMgO (hexagonal system, a = 0.325 nm), which can provide better lattice matching and suppress interfacial stress-induced dislocations and defects, improving the growth quality and performance of the ZnMgO ferroelectric thin film layer 530.
[0035] Upgrading the single Al2O3 buffer layer 520 to a graded composition Al x Zn 1-x O gradient layer (x from 1 to 0) is deposited by magnetron sputtering in sections to gradually match the lattice constant. This design reduces the interface stress, suppresses the interface defects caused by the diffusion of Si atoms, and optimizes the c-axis lattice constant of ZnMgO through strain regulation, thereby improving the ferroelectric phase transition temperature (Tc) and fatigue resistance, and solving the stress concentration problem between the buffer layer 520 and the thin film in the basic solution.
[0036] In an embodiment, in the atomic layer deposition process of step S2, diethyl zinc is used as the precursor of zinc, and bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium or diethyl magnesium is used as the precursor of magnesium, wherein the diethyl zinc is not subjected to heating treatment, and the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is heated to 135-145°C. Preferably, the heating temperature of the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is 140°C. The bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is heated to improve the volatilization efficiency and ensure a high enough vapor pressure.
[0037] If bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the precursor of magnesium, the large steric ligand bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is more complete in the decomposition process, and the residual carbon impurities are less than 0.5 at.%, which significantly reduces the carbon impurities and helps to improve the purity of the thin film and its electrical and optical properties. Due to the reduction of residual carbon impurities, the increase of leakage current caused by carbon impurities as carrier traps is avoided.
[0038] If diethyl magnesium is used as the precursor of magnesium, its lower decomposition temperature is adapted to the low-temperature process, and the carbon residue problem of the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium ligand is avoided. By increasing the carrier gas flow to 300 sccm, the risk of spontaneous combustion of diethyl magnesium is suppressed, and the volatile decomposition products ethylene and hydrogen can reduce the carbon impurities of the thin film, significantly improve the dielectric purity, while retaining the advantages of ALD atomic-level composition control, and are suitable for high-frequency device scenarios sensitive to impurities.
[0039] In some embodiments, when bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the precursor of magnesium, deionized water is used as the oxidation source; when diethyl magnesium is used as the precursor of magnesium, oxygen plasma is used as the oxidation source.
[0040] In some embodiments, in the atomic layer deposition process of step S2, the carrier gas is argon; when bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the magnesium precursor, the flow rate of the carrier gas ranges from 170 sccm to 230 sccm, preferably, the flow rate of the carrier gas is 200 sccm, and the system pressure ranges from 0.16 Torr to 0.18 Torr, preferably, the system pressure is 0.17 Torr; when diethyl magnesium is used as the magnesium precursor, the flow rate of the carrier gas ranges from 270 sccm to 330 sccm, preferably, the flow rate of the carrier gas is 200 sccm.
[0041] In the present scheme, high flow rate of the carrier gas is used to ensure that the precursors are quickly diffused into the complex structure, thereby reducing the deposition difference caused by the concentration gradient. In the 3D NAND structure, a bottom coverage of >95% can be achieved.
[0042] In one embodiment, in the atomic layer deposition process of step S2, a single cycle of ZnO includes the following processing steps in sequence: 0.05 s diethyl zinc pulse, 10 s argon purge, 0.05 s deionized water pulse, and 10 s argon purge.
[0043] In some embodiments, when bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the magnesium precursor, a single cycle of MgO includes the following processing steps in sequence: 0.8 s bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium pulse, 15 s argon purge, 0.05 s deionized water pulse, and 15 s argon purge.
[0044] When diethyl magnesium is used as the magnesium precursor, a single cycle of MgO includes the following processing steps in sequence: 0.8 s diethyl magnesium pulse, 15 s argon purge, 0.05 s deionized water pulse, and 15 s argon purge.
[0045] In the carrier gas purge process, argon is used to remove the physically adsorbed precursors and by-products, thereby reducing the non-stoichiometric defects (such as oxygen vacancies) and facilitating the formation of a well-crystallized ferroelectric phase (wurtzite structure). Long-time argon purge (15 s) can effectively remove the unreacted precursors, thereby preventing the component fluctuation caused by parasitic reactions.
[0046] By independently controlling the pulse time and cycle number of the Zn precursor and the Mg precursor, the Mg doping concentration (y value) in the ZnMgO thin film can be accurately adjusted, and the Mg content is a key factor for determining the ferroelectricity of ZnMgO (generally, y needs to be between 0.2 and 0.4 to form a ferroelectric phase), which meets the composition design requirements of the ferroelectric thin film. 1- y Mg y O thin film, and the Mg content is a key factor for determining the ferroelectricity of ZnMgO (generally, y needs to be between 0.2 and 0.4 to form a ferroelectric phase), which meets the composition design requirements of the ferroelectric thin film.
[0047] In the atomic layer deposition process, the pulse time of ZnO and MgO cycles is different (for example, the pulse time of the Mg precursor is longer, the pulse time of the Mg precursor is 0.8 s, which is greater than the pulse time of the Zn precursor, 0.05 s). The pulse time of the Mg precursor is extended to 0.8 s to ensure that the surface reaction is saturated and to avoid insufficient Mg incorporation.
[0048] In an embodiment, in the atomic layer deposition process of step S2, a single supercycle includes N times of ZnO cycles and 1 time of MgO cycle, where N is a positive integer. Depositing 50 supercycle ZnMgO ferroelectric film layers 530 reaches a thickness of about 50 nm.
[0049] The ZnO cycle is used to deposit ZnO, and the MgO cycle is used to deposit MgO. The content of Mg in the ZnMgO film can be adjusted by changing the value of N. N represents the number of ZnO cycles in one supercycle.
[0050] When N = 9, the content of Mg in the prepared ZnMgO ferroelectric film layer 530 is 10%, and each supercycle includes 9 times of ZnO cycles and 1 time of MgO cycle. The proportion of Mg in the ZnMgO ferroelectric film layer 530 is relatively low, mainly depositing ZnO, and a small amount of Mg is introduced.
[0051] When N = 4, the content of Mg in the prepared ZnMgO ferroelectric film layer 530 is 20%, and each supercycle includes 4 times of ZnO cycles and 1 time of MgO cycle. The proportion of MgO in the ZnMgO ferroelectric film layer 530 increases, and the proportion of Mg increases.
[0052] When N = 2, the content of Mg in the prepared ZnMgO ferroelectric film layer 530 is 33%, and each supercycle includes 2 times of ZnO cycles and 1 time of MgO cycle. The proportion of MgO in the ZnMgO ferroelectric film layer 530 is significantly improved, and the proportion of Mg is further increased.
[0053] When N = 1, the content of Mg in the prepared ZnMgO ferroelectric film layer 530 is 50%, and each supercycle includes 1 time of ZnO cycle and 1 time of MgO cycle. The proportion of MgO in the ZnMgO ferroelectric film layer 530 is close to 1:1, and the proportion of Mg is high.
[0054] By changing the number N of ZnO cycles in the supercycle, the content of Mg in the ZnMgO film can be accurately controlled. By adjusting the content of Mg, the ferroelectric properties of the ZnMgO film can be optimized. Different Mg contents will affect the crystal structure, dielectric constant, polarization strength, and other properties of the film. Through the alternative deposition mode of the supercycle, the uniform distribution of Mg in the film is ensured, and the performance unevenness caused by excessive or insufficient Mg in the local area is avoided.
[0055] In an embodiment, in the atomic layer deposition process of step S2, when deionized water is used as the oxidizing source, the deposition temperature ranges from 250°C to 400°C; when oxygen plasma is used as the oxidizing source, the deposition temperature ranges from 200°C to 300°C. High temperature promotes atomic migration, reduces point defects such as oxygen vacancies (Vo), reduces interface state density, and improves fatigue resistance.
[0056] If oxygen plasma is used as the oxidizing source, the substrate temperature can be reduced to 200-300°C, and high-energy oxygen radicals are used to promote complete reaction of the precursor. This improvement reduces the density of oxygen vacancies and induces the preferential growth of ZnMgO along the (0002) crystal direction by plasma energy, increases the size of ferroelectric domains, and increases the remanent polarization to P r, while solving the problem of insufficient crystallization at low temperature in traditional thermal ALD, and being compatible with more heat-sensitive substrates.
[0057] In an embodiment, after the supercycle deposition is completed, the ZnMgO ferroelectric thin film layer 530 is rapidly thermal annealed at 400°C for 10 min in an oxygen atmosphere to promote the crystallization of the ferroelectric phase.
[0058] In an embodiment, the top electrode layer 540 is indium tin oxide (ITO), and the thickness of the top electrode layer 540 is 50 nm.
[0059] In an embodiment, a quadrupole mass spectrometer (QMS) and a control adjustment system are integrated in the process chamber of the atomic layer deposition equipment. In the atomic layer deposition process of step S2, the quadrupole mass spectrometer monitors the signal intensity ratio of Zn and C2H6 and the signal intensity ratio of Mg and C4H 10 in the exhaust gas in real time, and the control adjustment system dynamically adjusts the precursor pulse time of zinc and the precursor pulse time of magnesium according to the monitoring results of the quadrupole mass spectrometer.
[0060] By monitoring the intensity ratio changes of these signals through the quadrupole mass spectrometer, the consumption of the precursors in the deposition process can be intuitively reflected. When the signal intensity ratio changes, it indicates that the consumption rate or vapor pressure of the precursors may have changed. In the long-term ALD deposition process, the vapor pressure of the precursors may gradually decrease due to consumption. The decrease in vapor pressure will lead to insufficient supply of precursors, thereby affecting the uniformity and composition stability of the thin film. By dynamically adjusting the precursor pulse time (such as extending the pulse time of THD magnesium from 0.8 s to 1.0 s), the supply of precursors can be increased to compensate for the attenuation of vapor pressure, ensuring the stability of the thin film deposition process.
[0061] By monitoring and feeding back the consumption of the precursor in real time, and automatically adjusting the pulse time to compensate for the changes. This automatic adjustment mechanism can effectively reduce the fluctuation of Mg content, improve the precise control of film composition. By monitoring the signal intensity ratio in the tail gas in real time, a warning can be given when the precursor is about to be exhausted, avoiding the interruption of deposition or film quality problems caused by the depletion of the precursor. By accurately controlling the amount of precursor supplied in each deposition cycle, the difference in film thickness between different batches can be reduced, solving the problem of component drift caused by the consumption of the precursor during long-term deposition, especially suitable for large-scale production scenarios.
[0062] The process of the method for preparing a ZnMgO ferroelectric thin film non-volatile memory by the ALD process of the application will be explained in detail below in combination with specific examples.
[0063] First, the substrate is prepared and pretreated. A p-type silicon wafer with a crystal orientation of 100 is selected, cleaned to remove organic matter and etched to remove the native oxide layer, and then a 50 nm thick Al2O3 buffer layer 520 is deposited on the cleaned silicon wafer surface by magnetron sputtering to improve lattice matching and suppress interface defects.
[0064] Next, the ZnMgO ferroelectric thin film is deposited by atomic layer deposition. The ALD deposition is carried out on the Si / Al2O3 substrate in a horizontal thermal ALD chamber. The substrate is located at the center of the chamber, and the heating temperature of the substrate ranges from 250°C to 400°C, preferably 300°C. Diethyl zinc and bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium are used as the precursors of Zn and Mg, respectively. Deionized water is used as the oxidizing source, and argon is used as the carrier gas. The content of Mg is controlled by supercycle design, wherein a single supercycle contains N times of ZnO cycle and 1 time of MgO cycle. For example, N = 4 corresponds to a Mg content of 20%, and 50 supercycles are deposited to achieve a thickness of about 50 nm. After deposition, rapid thermal annealing at 400°C for 10 minutes in an oxygen atmosphere is performed to promote the crystallization of the ferroelectric phase.
[0065] The performance test and characterization of the ferroelectric memory prepared by the method for preparing a ZnMgO ferroelectric thin film non-volatile memory by the ALD process of the application will be explained below.
[0066] The ferroelectric test system is used to measure the hysteresis loop to obtain the remanent polarization (Pr) and the coercive field (Ec), and the structure morphology is characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Regarding the testing process of a single ZnMgO nonvolatile memory, the Si / Al2O3 / ZnMgO / ITO prepared in the application is generally applicable to the ferroelectric analyzer on the market, and the test electrical signal result is a typical nonvolatile memory characteristic. The wurtzite structure (0002) diffraction peak signal can be seen from the XRD spectrum, and the SEM imaging diagram shows a rough surface.
[0067] In the application, through atomic-level control, interface optimization and three-dimensional compatible process of ALD, high-precision preparation of ZnMgO FeRAM device is realized. The process method has simple steps, short cycle, low preparation cost, high yield of finished devices, strong compatibility with CMOS process, and is suitable for industrial production and mass production.
[0068] Compared with the prior art, the application has the following technical effects: The technical problem to be solved by the application is how to prepare a wurtzite zinc magnesium oxygen ferroelectric material by atomic layer deposition technology and apply it to a storage medium layer of a nonvolatile memory, design and prepare a Si / Al2O3 / ZnMgO / ITO device structure, so as to realize a stable nonvolatile ferroelectric memory. Compared with the existing zinc magnesium oxygen ferroelectric film preparation technology, such as radio frequency magnetron sputtering and chemical solution deposition, the application aims to improve the quality of the wurtzite zinc magnesium oxygen film, such as reducing defects, improving component uniformity, adapting to high aspect ratio structures, etc., to realize a nonvolatile ferroelectric memory with higher performance. As a new type of ferroelectric material, zinc magnesium oxygen has high spontaneous polarization, low leakage current density, high Curie temperature, good compatibility with semiconductor manufacturing process and other characteristics, and has great potential in the field of nonvolatile memories. The process method of the application has simple steps, low preparation cost, high yield of finished devices on a 2-inch amorphous silicon wafer, strong compatibility with traditional CMOS process, and is suitable for industrial mass production. The ferroelectric memory prepared by the application has higher remanent polarization than the traditional ferroelectric memory produced by the prior art. The high remanent polarization realized by the application has certain research value for realizing high-density storage units.
[0069] In the description of the application, it should be understood that the terms "include" and "have" and any variations thereof used in this paper are intended to cover non-exclusive inclusion, for example, a process, method, system, product or equipment including a series of steps or units does not have to be limited to those steps or units clearly listed, but can include other steps or units not clearly listed or inherent to these processes, methods, products or equipment.
[0070] It should be understood that the terms "length", "width", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer" and the like, specify relative positions or orientations of an apparatus or element as shown in the drawings, and are used only for convenience in describing the present application and simplifying the description, and thus can not be construed as indicating or implying that a specific orientation is required for the application to function or is an essential feature of the application, and therefore should not be understood as limiting the application.
[0071] In addition, the terms "first", "second", etc., are used herein only to describe various conditions, and should not be construed as indicating or implying relative importance or a specific number of the indicated technical features. Thus, the features defined with "first", "second" can explicitly or implicitly include one or more of the features. In the description of the present application, the meaning of "a plurality of" is two or more, unless otherwise specified.
[0072] Although the embodiments of the present application have been described in detail above, it should be apparent to those skilled in the art that various modifications and changes can be made thereto without departing from the spirit and scope of the application as set forth in the appended claims. Moreover, the present application is not to be limited by the embodiments described herein, but can be practiced with variations within the scope of the appended claims. Unless otherwise defined, scientific and technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
Claims
1. A method of fabricating a ZnMgO ferroelectric thin film nonvolatile memory by an ALD process, characterized in that, The method comprises the following steps: S1: forming a buffer layer on a p-type silicon substrate by a magnetron sputtering process; S2: depositing a ZnMgO ferroelectric film layer on the buffer layer by an atomic layer deposition process; S3: depositing a top electrode layer on the ZnMgO ferroelectric film layer, and performing a patterning treatment on the top electrode layer by a photolithography and stripping process, and exposing part of the ZnMgO ferroelectric film layer; S4: performing a patterning treatment on the exposed part of the ZnMgO ferroelectric film layer by a photolithography and stripping process, and finally forming a ferroelectric memory.
2. The method of claim 1, wherein the ALD process is performed at a temperature of 300-600 °C. Diethyl zinc is used as the zinc precursor, and bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium or diethyl magnesium is used as the magnesium precursor, wherein the diethyl zinc is not subjected to heating treatment, and the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is heated at a range of 135-145 DEG C.
3. The method of claim 2, wherein the ALD process is performed at a temperature of 300-600 °C. When the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the magnesium precursor, deionized water is used as the oxidizing source; When the diethyl magnesium is used as the magnesium precursor, oxygen plasma is used as the oxidizing source.
4. The method of claim 2, wherein the ALD process is performed at a temperature of 300-600 °C. In the atomic layer deposition process of step S2, the carrier gas is argon; When the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the magnesium precursor, the flow rate of the carrier gas ranges from 170 sccm to 230 sccm, and the system pressure ranges from 0.16 Torr to 0.18 Torr; When the diethyl magnesium is used as the magnesium precursor, the flow rate of the carrier gas ranges from 270 sccm to 330 sccm.
5. The method of claim 2, wherein the ALD process is performed at a temperature of 300-600 °C. In the atomic layer deposition process of step S2, a single ZnO cycle comprises the following treatment steps in sequence: 0.05 s diethyl zinc pulse, 10 s argon purge, 0.05 s deionized water pulse, and 10 s argon purge.
6. The method of claim 5, wherein the ALD process is performed at a temperature of 300-600 °C. When the bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium is used as the magnesium precursor, a single MgO cycle comprises the following treatment steps in sequence: 0.8 s bis(2,2,6,6,-tetramethyl-3,5-heptanedionate) magnesium pulse, 15 s argon purge, 0.05 s deionized water pulse, and 15 s argon purge; When the diethyl magnesium is used as the magnesium precursor, a single MgO cycle comprises the following treatment steps in sequence: 0.8 s diethyl magnesium pulse, 15 s argon purge, 0.05 s deionized water pulse, and 15 s argon purge.
7. The method of claim 6, wherein the ALD process is performed at a temperature of 300-600 °C. In the atomic layer deposition process of step S2, a single super cycle comprises N times of ZnO cycles and 1 time of MgO cycle, and the doping concentration of magnesium in the ZnMgO film can be adjusted by controlling the pulse time of the zinc precursor, the pulse time of the magnesium precursor, and the cycle number N, wherein N is a positive integer.
8. The method of claim 7, wherein the ALD process is performed at a temperature of 300-600 °C. After the super cycle deposition is completed, the ZnMgO ferroelectric film layer is subjected to rapid thermal annealing at 400 DEG C in an oxygen atmosphere for 10 min.
9. The method of claim 2, wherein the ALD process is performed at a temperature of 300-600 °C. The process cavity of the atomic layer deposition device is integrated with a quadrupole mass spectrometer and a control adjustment system. In the atomic layer deposition process of step S2, the quadrupole mass spectrometer monitors the signal intensity ratio of Zn and C2H6 and the signal intensity ratio of Mg and C4H 10 in the tail gas in real time, and the control adjustment system dynamically adjusts the precursor pulse time of zinc and the precursor pulse time of magnesium according to the monitoring result of the quadrupole mass spectrometer.
10. The method of claim 1, wherein the ALD process is used to fabricate ZnMgO ferroelectric thin film nonvolatile memory, and wherein the ZnMgO ferroelectric thin film nonvolatile memory is characterized by: The buffer layer is an Al2O3 layer, a ZnO layer, or a gradient component Al x Zn 1-x O gradient layer, wherein x is greater than 0 and less than 1.
